Karakteristik Protein dan Nitrogen Non Protein Daging Ikan Cucut Lanyam (Charcharhinus limbatus) (Characteristics of Protein and Non Protein Nitrogen in Lanyam Shark Muscle) - Yuspihana Fitrial (Faculty of Fisheries and Marine Resources of Lambung Mangkurat University-South Kalimantan, 2011)
The aim of these research were to study the characteristics of protein and non protein nitrogen contained in Lanyam shark muscle, to obtain the protein solubility curve and iso-electric point. This research begins with the analysis of protein solubility of shark muscle at several levels of pH (from 1.5-12 with intervals of 0.5),. Then, performed classification of shark muscle protein nitrogen solubility in some solvents by using the classification Osborn, to observed the influence of the process of washing and boiling on non-protein nitrogen and urea in shark muscle and to study the thermal stability of muscle protein with differential scanning calorimetric study. Based on protein solubility of Lanyam muscle at pH 1.5 to 12 obtained two points which is minimum solubility at pH 4.5 and pH 9. Based on the classification Osborn, Lanyam muscle contained albumin (28.64%), globulin (13:44%), prolamin (03.29%), glutelin (33.70%). Observation of non-protein nitrogen levels indicated that the washing process was very effective to reduce non-protein nitrogen levels up to 62.34% and urea levels up to 58% . Differential Scanning Calorimetry Study of Lanyam mince showed two types of protein that has a different stability to heat and after added 2.5% NaCl formed a peak which is a fusion of both these proteins